Answer:
C. x - y = 0
Explanation:
Step 1: find the slope (m) and y-intercept (b) of the graphed line.
Using the two points on the line (0, 0) and (2, 2),
Slope =
![(rise)/(run) = (2 - 0)/(2 - 0) = (2)/(2) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/qk6kxiuk23gkllrb3w85hvrs8rfzw3p5ld.png)
The y-intercept (b) is the point at which the line intercepts the y-axis. Therefore, the y-intercept (b) = 0
Step 2: Generate an equation for the line in slope-intercept form using b = 0 and m = 1.
Substitute m = 1 and b = 0 into y = mx + b
y = 1(x) + 0
y = x
Step 3: rewrite the equation from slope-intercept form to standard form.
To express I'm standard form, take all terms with coefficient to the left, and leave the constant on the right side of the equation.
y = x
Subtract y from both sides
y - y = x - y
0 = x - y
x - y = 0